Object-oriented construction handbook : developing application-oriented software with the tools & materials approach - Zullighoven, Heinz (Elsevier ; Morgan Kaufmann ; Dpunkt.verlag, 2005)
Successful businesses and organizations are continually looking for ways to improve service and customer satisfaction in order to achieve long-term customer loyalty. In light of these goals, software developers must ask the question: how does customer orientation influence traditional approaches, methods, and principles of software development? In this book, a leading software architect and his team of software engineers describe how the idea of customer orientation in an organization leads to the creation of application-oriented software. This book describes what application-oriented software development is and how it can be conceptually and constructively designed with object-oriented techniques. It goes further to describe how to best fit together the many different methodologies and techniques that have been created for object-orientation (such as frameworks, platforms, components, UML, Unified Process, design patterns, and eXtreme Programming) to design and build software for real projects. This book brings together the best of research, development, and day-to-day project work to the task of building large software systems. *Written by and for developers of large, interactive, and long-lived software systems *Includes patterns of proven analysis, design, and documentation techniques *Shows how to develop an appropriate design approach and concrete software development techniques.